Fighting the next pandemic: A phytochemical Approach from African flora - An overview - Buyinza, Daniel; Gumula, Ivan (Society for the Advancement of Scienvce in Africa, 2025)
Management of any pandemic requires a multidimensional approach with a hand from all players. At every break of a pandemic, there is always no immediate treatment and efforts are often devoted to social distancing, isolation/quarantine, diagnosis, and care with prospects to treat but with no clear medication. The approach has always been to permit the body to fight off the pandemic by boosting its immune system through selective diet and or food supplements as external immune boosters in addition to arresting symptoms. With the exception of COVID-19, the burden of HIV epidemic and seasonal flu pandemics, infectious disease outbreaks have mostly devastated developing societies. The use of herbal remedies to cure several kinds of human diseases has a long history in Africa. Various plant parts are used to prevent, dispel symptoms or regress deformities to normal. A portion of the pharmaceutical products currently being prescribed by physicians including opium, aspirin, digitalis, paclitaxel, docetaxel, vinblastine, vincristine, quinine, and artemisinin have a historic use as herbal remedies. African medicinal plants are rich in such natural bioactive metabolites with therapeutic values against several diseases including deadly fevers. The therapeutic properties of these metabolites are a factor of the type and amount of alkaloids, phenolics, flavonoids, quinones, saponins, and terpenes contained. Human ingestion of these bioactive trigger pharmacological effects like antiviral, anti-inflammatory, analgesic, antidiabetic, antimicrobial, anti-parasitic, and antioxidant effects, thereby arresting the causal or symptomatic effects manifested in the pandemics. Ethnomedical and phytochemical studies on the African medicinal plants have led to the isolation of promising antiviral, anti-inflammatory, anti-parasitic, analgesic, and antimicrobial metabolites. Our discussion in this chapter is premised on challenging Africans Scientists (ethnobotanists, phytochemists, microbiologists, and pharmacologists) to collaboratively intensify the search for phytochemicals as drug leads and explore options for developing these leads into functional medicines for the various diseases/pandemics devastating the continent.